Where do tuberculosis patients go for treatment before reporting to DOTS clinics in southern Nigeria - Okeibunor, JC; Onyeneho, NG; Chukwu, JN; Post, E (Tanzania Journal of Health Research, 2007)
No Abstract. Tanzania Health Research Bulletin Vol. 9(2) 2007: pp.94-101